Más allá de un sustituto de la motivación (2019)
The image of man as presented in the predominant organizational theories of motivation does not accord with the author’s experience of working with people in organizations. This dissonance has led to a critique of the concept of motivation and its inherent theoretical shortcomings as to the reality of people in organizations. The main argument of this essay, however, stems from a metacritical perspective according to which the notion of motivation and its referrant theories can be regarded as scientific inventions. The hypothesis is offered and elaborated that motivation is a surrogate for meaning, i.e. for the meaning of work and life which is increasingly lost through the high frequency of fragmentation and splitting in our contemporary work enterprises. Any attempt towards discovering existential dimensions of meaning can be accomplished only if social scientists, managers and workers alike, both individually as well as collectively, again become aware of death as a fact of life; it is only through acknowledging mortality that humanization can occur.